2006
DOI: 10.1182/blood-2005-04-1513
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of HIV-specific CD4+ and CD8+ T cells by dendritic cells transfected with mRNA encoding cytoplasm- or lysosome-targeted Nef

Abstract: Transfection with synthetic mRNA is a safe and efficient method of delivering antigens to dendritic cells for immunotherapy. Targeting antigens to the lysosome can sometimes enhance the CD4 ؉ T-cell response. We transfected antigenpresenting cells (APCs) with mRNA encoding Gag-p24 and cytoplasmic, lysosomal, and secreted forms of Nef. Antigenspecific cytotoxic T cells were able to lyse the majority of transfected targets, indicating that transfection was efficient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
45
1
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 31 publications
(45 reference statements)
2
45
1
1
Order By: Relevance
“…Immunization against native simian HIV Ags with DNA or vaccinia virus preparations has been shown to increase the breadth of the CTL response after simian HIV challenge (68), and it is possible that endosomal/lysosomal targeting, such as that provided by the LAMP/gag or DC-LAMP/gag chimeras, could further enhance the diversity of the epitope response. Finally, Kavanagh et al (69) recently showed that DC transfected with HIV Nef targeted to the lysosome by LAMP was able to expand a greater repertoire of T cells from HIV patients than the DC transfected with HIV Nef. These results imply that LAMP-targeted Ag generated a greater or distinct repertoire of peptides than the native Nef, and it was considered as a promising approach to HIV immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Immunization against native simian HIV Ags with DNA or vaccinia virus preparations has been shown to increase the breadth of the CTL response after simian HIV challenge (68), and it is possible that endosomal/lysosomal targeting, such as that provided by the LAMP/gag or DC-LAMP/gag chimeras, could further enhance the diversity of the epitope response. Finally, Kavanagh et al (69) recently showed that DC transfected with HIV Nef targeted to the lysosome by LAMP was able to expand a greater repertoire of T cells from HIV patients than the DC transfected with HIV Nef. These results imply that LAMP-targeted Ag generated a greater or distinct repertoire of peptides than the native Nef, and it was considered as a promising approach to HIV immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we (47,48,61) and others (9,15,22,28,40,54,57) have shown that transfection with mRNA is more effective than mRNA lipofection, peptide pulsing, or viral transduction to generate primary (65) and memory (57) responses. Furthermore, we demonstrated that DC from treatment-naïve HIV-1-seropositive subjects can efficiently be transfected with HIV gag and env mRNA, derived either from consensus subtype B or autologous viral or proviral HIV, and that these DC readily trigger autologous CD4 ϩ and CD8 ϩ T cells to release IFN-␥ and IL-2 in a short-term ex vivo enzyme-linked immunospot (ELISPOT) assay (60).…”
mentioning
confidence: 99%
“…DNA transfection of DC has been used successfully in some studies but is limited by poor expression levels and toxicity (2,29,41,45,49), although methods to enhance expression based on DC maturation have been proposed (28). mRNA transfection of DC is being increasingly utilized for cancer immunotherapy and in vitro stimulation of virus-specific T cells, but approaches to deliver mRNA into primary DC cultures have been limited (16,18,25,39,40,43,48,50). Transfection of DC with mRNA offers the potential for highlevel expression of wild-type viral transgenes that have poor expression in mammalian cells when traditional methods of gene delivery are used (8,26).…”
mentioning
confidence: 99%